Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/iae.0b013e3182947b29
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Combined 1.8-MM Microincision Cataract Surgery and 23-Gauge Transconjunctival Vitrectomy for Posterior Segment Disease

Abstract: Combined sutureless coaxial microincision cataract surgery and 23-gauge vitrectomy offers the advantages of both coaxial microincision cataract surgery (less wound leakage, good anterior chamber stability, and safety) and 23-gauge vitrectomy (decreased inflammation and faster rehabilitation after surgery).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…In the present study, none of the eyes from the C‐MICS group required suturing of the corneal wound in accordance with our previous findings, which indicated that 1.8‐mm corneal incision offers very good AC stability, even under excessive manipulation of the globe during surgery (Czajka et al. ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, none of the eyes from the C‐MICS group required suturing of the corneal wound in accordance with our previous findings, which indicated that 1.8‐mm corneal incision offers very good AC stability, even under excessive manipulation of the globe during surgery (Czajka et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…Only one eye in this study (3%) developed iris posterior synechiae postoperatively, similar to previous studies of combined C‐MICS and vitrectomy with low incidence (Czajka et al. ; Jalil et al. ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations